Book Review: Thanos Zartaloudis, "The Birth of Nomos", Edinburgh: Edinburgh University Press, 2019 - Skarbek-Kazanecki, Jan (Collectanea Philologica, 2021)
This paper contains a critical assessment of the The Birth of Nomos (Edinburgh: Edinburgh University Press, 2019) of Thanos Zartaloudis. It describes the key assumptions made in this recent publication, as well as the content of each chapter, judging on its merits and defects.